Capacity Study Of A Food Processing Company Using Arena Simulation Software - Sh Ahmad, Sh Salleh; Abu Kasim, Abdul Syukur; Masood, Ibrahim; Ho, Fu Haw; Abdullah, Haslina (Research Progress in Mechanical and Manufacturing Engineering, 2021)
Small and medium enterprises (SME) contribute significantly to the country's growth, especially in the food manufacturing industry sector. Fast Kitchen Sdn. Bhd. Parit Raja is one of the SME for food processing company that is currently having problem to achieve the daily output in meeting the demand. The lack of standard production rate as the main indicator in the management may lead to the problem that occurred. The aim of the study was to build and simulate the Arena Simulation model for the production process of the food processing company and to analyse the capacity of the production process using the simulation report. The data was collected based on the actual production line to be inserted into the system setting for validation purpose. The model was run for the 10 replications to achieve accuracy in the result. The alternative models were then developed with different configurations to improve the production capacity. This was done by observing the simulation result that would provide higher production output within acceptable resource utilization. This study indicated the productivity improvement between 5.11% to 21.47% can be achieved through minor manipulation of working time or additional one manpower. Overall, the simulation finding could be a guideline for the owner to decide for any improvement in their production capability.